The Leadership Role of the Principal in Increasing Early Chilhood Creativity Activities at Pertiwi Kindergarten Indralaya Ogan Ilir South Sumatra - Sartika, Dewi; Ahyani, Nur; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to identify and describe: (1) The Leadership role of the principal in increasing early childhood creativity activities; (2) Steps to achieve the goal of increasing the creativity of early childhood; (3) Supporting and inhibiting factors for early childhood creativity. The method used in this research is qualitative. Data collection techniques through observation, interviews and documentation. The data analysis technique in this study is an interactive model analysis technique with data analysis procedures covering three stages, namely: data reduction, data presentation and conclusion drawing, and verified through data validity techniques by triangulation. The results of this study concluded that in carrying out activities to increase the creativity of early childhood in Pertiwi Indralaya Kindergarten, the leadership role of the school principal and good cooperation from teachers and student guardians cannot be separated. The inhibiting factors of creative activities are inadequate infrastructure and the curriculum used is still using curriculum 2013.